Fetal hydrops and the Incremental yield of Next‐generation sequencing over standard prenatal Diagnostic testing (FIND) study: prospective cohort study and meta‐analysis. (1st October 2021) - Mone, F.; Eberhardt, R. Y.; Hurles, M. E.; Mcmullan, D. J.; Maher, E. R.; Lord, J.; Chitty, L. S.; Dempsey, E.; Homfray, T.; Giordano, J. L.; Wapner, R. J.; Sun, L.; et al.
ABSTRACT: Objective: To determine the incremental yield of exome sequencing (ES) over chromosomal microarray analysis (CMA) or karyotyping in prenatally diagnosed non‐immune hydrops fetalis (NIHF). Methods: A prospective cohort study (comprising an extended group of the Prenatal Assessment of Genomes and Exomes (PAGE) study) was performed which included 28 cases of prenatally diagnosed NIHF undergoing trio ES following negative CMA or karyotyping. These cases were combined with data from a systematic review of the literature. MEDLINE, EMBASE, CINAHL and ClinicalTrials.gov databases were searched electronically (January 2000 to October 2020) for studies reporting on the incremental yield of ES over CMA or karyotyping in fetuses with prenatally detected NIHF. Inclusion criteria for the systematic review were: (i) at least two cases of NIHF undergoing sequencing; (ii) testing initiated based on prenatal ultrasound‐based phenotype; and (iii) negative CMA or karyotyping result. The incremental diagnostic yield of ES was assessed in: (i) all cases of NIHF; (ii) isolated NIHF; (iii) NIHF associated with an additional fetal structural anomaly; and (iv) NIHF according to severity (i.e. two vs three or more cavities affected). Results: In the extended PAGE study cohort, the additional diagnostic yield of ES over CMA or karyotyping was 25.0% (7/28) in all NIHF cases, 21.4% (3/14) in those with isolated NIHF and 28.6% (4/14) in those with non‐isolated NIHF. In the meta‐analysis, the pooled incremental yield based on 21 studies (306 cases) was 29% (95% CI, 24–34%; P < 0.00001; I 2 = 0%) in all NIHF, 21% (95% CI, 13–30%; P < 0.00001; I 2 = 0%) in isolated NIHF and 39% (95% CI, 30–49%; P < 0.00001; I 2 = 1%) in NIHF associated with an additional fetal structural anomaly. In the latter group, congenital limb contractures were the most prevalent additional structural anomaly associated with a causative pathogenic variant, occurring in 17.3% (19/110) of cases. The incremental yield did not differ significantly according to hydrops severity. The most common genetic disorders identified were RASopathies, occurring in 30.3% (27/89) of cases with a causative pathogenic variant, most frequently due to a PTPN11 variant (44.4%; 12/27). The predominant inheritance pattern in causative pathogenic variants was autosomal dominant in monoallelic disease genes (57.3%; 51/89), with most being de novo (86.3%; 44/51). Conclusions: Use of prenatal next‐generation sequencing in both isolated and non‐isolated NIHF should be considered in the development of clinical pathways. Given the wide range of potential syndromic diagnoses and heterogeneity in the prenatal phenotype of NIHF, exome or whole‐genome sequencing may prove to be a more appropriate testing approach than a targeted gene panel testing strategy. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.